2001
DOI: 10.2169/internalmedicine.40.331
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol Hypersensitivity Syndrome Associated with Systemic Cytomegalovirus Infection and Systemic Bacteremia.

Abstract: A 43-year-old man developed fever, skin rash, eosinophillia, and severe renal and liver dysfunction following treatment with allopurinol. The patient died after 3 months of hospitalization. Autopsy revealed systemic cytomegalovirus infection and bacteremia. (Internal Medicine 40: 331-335, 2001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Early or late scores $4 were associated with the later development of CMV disease and complications (Table III). Receiver operator characteristic curves confirmed that this composite score had the Arrhythmia (1), brain tumor (2), bullous disease (1), cerebrovascular disease (1), dementia (1), epilepsy (2), GuillaineBarre syndrome (1), and hyperuricemia (3) Brain tumor (1), cerebrovascular disease (2), epilepsy (12), fibromyalgia (1), hyperuricemia (7), neuralgia (3), psychological illness (17), and restless legs syndrome (1) Causative drug (n)…”
Section: Cmv-related and -Unrelated Complicationsmentioning
confidence: 85%
See 3 more Smart Citations
“…Early or late scores $4 were associated with the later development of CMV disease and complications (Table III). Receiver operator characteristic curves confirmed that this composite score had the Arrhythmia (1), brain tumor (2), bullous disease (1), cerebrovascular disease (1), dementia (1), epilepsy (2), GuillaineBarre syndrome (1), and hyperuricemia (3) Brain tumor (1), cerebrovascular disease (2), epilepsy (12), fibromyalgia (1), hyperuricemia (7), neuralgia (3), psychological illness (17), and restless legs syndrome (1) Causative drug (n)…”
Section: Cmv-related and -Unrelated Complicationsmentioning
confidence: 85%
“…Complications occurring during DiHS/DRESS have been extensively described in previous studies [5][6][7][8][9][10][11][12][13][14] and have received attention as the cause of mortality in DiHS/DRESS. These complications include myocarditis, Pneumocystis jirovecii pneumonia, sepsis, and gastrointestinal bleeding, 5-14 most of which lead to significant morbidity and mortality if unrecognized and untreated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports have suggested that reactivation of other members of the herpesvirus family, including HHV‐7, 1,10,11 CMV 4,6 and EBV, 3 may also be involved in the pathomechanisms of DIHS. Furthermore, multiple viral reactivation 11,12 and sequential viral reactivation 10,13 have been reported in some cases of DIHS. In the present study, multiviral reactivation was observed in all seven patients: HHV‐6, HHV‐7, CMV and EBV were reactivated in one patient; HHV‐6, HHV‐7 and CMV in four patients; HHV‐6, CMV and EBV in one patient; and HHV‐6 and CMV in one patient.…”
Section: Discussionmentioning
confidence: 99%